I submitted the following but people were not reading the negative sign before the -9, so here it is 6-(-9f)<-3. I don't know if I make the -9f positive since there is a negative sign in front or what to do first. Thank you

6 - (-9f) < -3

Yes, the -(-9f) becomes a +9f:

6 + 9f < -3

9f < -9 [Subtracted 6 from both sides]

**f < -1**[Divided both sides by 9]

Check:

f=-1: 6-(-9(-1)) = 6-(9) = -3, which is equal to but not less than -3 as expected (since f ≥ -1)

f=-2: 6-(-9(-2)) = 6-18 = -12 which is less than -3 as expected (since f < -1)

f=0: 6-(-9(0)) = 6-0 = 6 which is > -3 as expected (since f > -1)

Graph:

-3 -2 -1 0 1 2

**<=|==|==**o--|--|--|->